A Case of Metastatic Breast Cancer to the Urinary Bladder - Sarah Sherman; Lindsay Lee; Charlotte Chaiklin (Annals of Internal Medicine: Clinical Cases)
Metastatic breast cancer to the urinary bladder is uncommon. We report a case of lobular carcinoma of the breast presenting as a urinary bladder tumor. Urinary bladder metastases usually are present in the setting of widespread metastatic disease and confer a poor prognosis. Invasive lobular carcinoma has a greater predilection to spread to serosal and peritoneal surfaces compared with other histologic types. Loss of cellular adhesion contributes to local and distant spread. In patients with a history of breast cancer, particularly lobular carcinoma, who present with a bladder mass, metastatic disease is an important consideration for timely diagnosis and treatment.